Poor survival on an artificial diet of two genotypes of the aphid Myzus persicae: a fitness cost of insecticide resistance?. (6th April 2014) - van Emden, Helmut F.; Foster, Stephen P.; Field, Lin M.
Abstract A fully susceptible genotype (4106A) of Myzus persicae survived the longest on an artificial diet and, in several of the eight replicates, monitoring was terminated when the culture was still thriving. A genotype with elevated carboxylesterase FE4 at the R3 level (800F) had a mean survival of only 98.13 days, whereas 794J, which combines R3 E4 carboxylesterase with target‐site resistance (knockdown resistance), survived for the even shorter mean time of 84.38 days. The poorer survival of the two genotypes with extremely elevated carboxylesterase‐resistance was not the result of a reluctance to transfer to new diet at each diet change. Although available for only two replicates, a revertant clone of 794J (794Jrev), which has the same genotype as 794J but the amplified E4 genes are not expressed leading to a fully susceptible phenotype, did not appear to survive any better than this clone. This suggests that the poor survival on an artificial diet of the extreme‐carboxylesterase genotypes is not the result of the cost of over‐producing the enzyme. The frequency of insecticide‐resistant genotypes is low in the population until insecticide is applied, indicating that they have reduced fitness, although this does not necessarily reflect a direct cost of expressing the resistance mechanism.